Gestión financiera de la empresa Colbapi S.A. de los periodos 2020 -2021. - Gavilánez Chaguay, Joyce Melany (2022)
This case study focuses on how the financial management of the company Colbapi SA was affected during the COVID-19 pandemic. It is known that this epidemic had a dangerous and serious meaning in the field of health and the economy; Since when a health emergency began, there were restrictions on movement and social relations, which created that the commercial area of Ecuador was affected; So much so that many companies had to close their businesses due to their low sales levels, others looked for ways to adopt financial sustainability. Due to the health situation that arose, the objective was to analyze the financial statements of the company in order to examine the financial management in the company Colbapi S.A during the period of 2020-2021. The methodology applied in this present investigation is the descriptive and quantitative methodology, in which the financial statements are analyzed and the observed characteristics of the period in question are reported, which gave me the necessary information on the financial statements, their sales to carry out the present case study, for which the reason was found from the effect created and for which the information presented was analyzed.